2010
DOI: 10.18060/266
|View full text |Cite
|
Sign up to set email alerts
|

Does Ethnicity Matter? Social Workers’ Personal Attitudes and Professional Behaviors in Reporting Child Maltreatment

Abstract: This study examined differences in the attitudes of professional social workers regarding corporal punishment and the perception and reporting of child maltreatment, according to the worker’s ethnic group membership (Asian, Black American, Black Caribbean, Hispanic, and non-Hispanic White). Data were obtained by mailed questionnaires from 808 members of the New York City chapter of NASW. Data were analyzed by analysis of variance. Results indicate that approval of corporal punishment and perception of maltreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…Finkelhor & Turner, 2009;Stoltenborgh et al, 2014). However, since perception of maltreatment is subjective, therefore differing across cultural, racial, ethnic backgrounds, and developmental stages (Ashton, 2010;Shanalingigwa, 2009), it is of particular interest to broaden the understanding of perceptions of maltreatment among adults and youth. For example, Saifan, Alrimawi, and Bashayreh (2015), who examined Palestinian nurses' perceptions of child maltreatment, reported that most nurses did not know how to handle with child abuse survivors effectively and found it hard to differentiate between violent physical and psychological disciplinary practices and child abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Finkelhor & Turner, 2009;Stoltenborgh et al, 2014). However, since perception of maltreatment is subjective, therefore differing across cultural, racial, ethnic backgrounds, and developmental stages (Ashton, 2010;Shanalingigwa, 2009), it is of particular interest to broaden the understanding of perceptions of maltreatment among adults and youth. For example, Saifan, Alrimawi, and Bashayreh (2015), who examined Palestinian nurses' perceptions of child maltreatment, reported that most nurses did not know how to handle with child abuse survivors effectively and found it hard to differentiate between violent physical and psychological disciplinary practices and child abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Les travailleurs sociaux s'adapteraient à la norme professionnelle sans y adhérer parce qu'ils sont clairvoyants et/ou parce qu'ils veulent rendre leurs publics clairvoyants. Enfin, le processus de socialisation à la culture professionnelle explique sans doute aussi en partie ce résultat (Ashton, 2010). Des recherches supplémentaires sur les processus explicatifs sous-jacents seraient nécessaires pour mieux comprendre les résultats obtenus.…”
Section: Discussionunclassified
“…Ainsi, ils peuvent rencontrer des difficultés à mettre en cohérence leurs pratiques professionnelles avec d'une part, les normes professionnelles en vigueur dans l'institution qui les emploie et, d'autre part, leurs croyances personnelles (Roquejoffre, 2011). Les attitudes et opinions personnelles qui influencent les pratiques sont tempérées par les normes, valeurs et par l'éthique de la profession acquises au cours du processus de socialisation professionnelle (Ashton, 2010 ;Hantman et al, 2006 ;Tam & Coleman, 2009). Les objectifs de cette recherche sont 1) de mesurer les préférences acculturatives personnelles, professionnelles et normatives des travailleurs sociaux dans le contexte des missions locales et 2) d'examiner, dans une perspective exploratoire, les rôles respectifs des croyances personnelles et de la norme professionnelle en matière de préférence acculturative sur les pratiques des travailleurs sociaux dans le champ de l'insertion professionnelle.…”
Section: Introductionunclassified
“…Croxton, Jayrante, & Mattison, 2002); ethnicity (i.e. Ashton, 2010;Schulte & Battle, 2004); motivation to enter into social work education (i.e. Osteen, 2011); students' willingness to self-reflect and change (Pugh, 1998); and religion (i.e.…”
Section: Social Work Education and Students' Beliefsmentioning
confidence: 99%